OPTIMIZATION AND EVALUATION OF QUALITY OF THE PEARL MILLET NUTRI WAFFLES - P. PRIYA; E. R ANEENA,SEEJA THOMACHAN; P. S LAKSHMY; P. PRAMEELA (The Journal of Research ANGRAU, 2023)
The study was carried out (2019-2022) to formulate nutritionally superior waffles with pearl millet. Pearl millet was used as the major ingredient in varying proportions starting from 90% to 50% along with 10% to 50% refined wheat flour and tapioca flours. Based on the organoleptic evaluation, nutri waffles prepared with pearl millet flour and refined wheat flour (RWF), PWT3 (70% PMF + 30% RWF) had good sensory qualities. Pearl millet centered nutri waffles with tapioca flour (TF), the treatment PTT4 (60% PMF + 40% TF) secured the top mean score of 8.47 for overall acceptability. The study showed the scope for value addition of pearl millet for nutri waffles incorporated with refined wheat flour and tapioca flour.